Legitimising corporate sustainability reporting throughout the world - Faisal, F.; Tower, Greg; Rusmin, Rusmin (University of Wollongong, 2012)
This paper explores corporate sustainability disclosure practices in a global context. A unique sample of 2009 sustainability reports from some of the world’s largest companies in 24 diverse countries are examined using a comprehensive disclosure index. These reports are analysed to better understand how company characteristics and institutional factors explain sustainability communication using a legitimacy theory framework. The world renowned Global Reporting Initiative 2006 guidelines are used as the benchmark disclosure index checklist. The empirical results indicate that the average level of sustainability disclosure is a surprisingly high 61.9 percent. Statistical analysis indicates that high profile industries and additional assurance procedures influence the disclosure of more sustainability information. Interestingly, companies operating in emerging country systems disclose more sustainability information than Anglo-Saxon or Communitarian jurisdictions. Consistent with legitimacy theory, these results suggest that these globally well known firms use sustainability disclosure as a legitimising tool.